Peran Masyarakat dalam Pembangunan Berkelanjutan Berwawasan Lingkungan pada Sektor Industri Kehutanan - Fitri Yanni Dewi Siregar (Mahesa Research Center, 2022)
Environmentally sound development is a conscious and planned effort that integrates the environment, including resources, into the development process to ensure the ability, welfare, and quality of life of present and future generations. This study aims to determine the importance of community participation in environmentally sustainable development in the forestry industry sector as a form of prevention and eradication of forest destruction and to increase public awareness about the importance of forest conservation and the negative impacts of forest destruction. The research method used is a normative juridical approach based on primary legal materials using data collection techniques through document studies which are then analyzed qualitatively. In this study it can be concluded that community participation is an absolute must in the framework of creating a healthy living environment as regulated in several laws and regulations and optimizing community participation in environmental protection and management activities by providing wider space for the community to participate.